The acceptance and adoption of technology on government environment: a bibliometric analysis - Hildawati, Hildawati; Wallang, Muslimin; Khairri Shariffuddin, Mohd Dino (Institute of Advanced Engineering and Science, 2025)
This study examines technology acceptance and adoption in government, particularly in the context of public service delivery, through a bibliometric analysis conducted using VOSviewer. The analysis aims to identify key research trends, thematic relationships, and emerging patterns in the field of digital governance. Data were retrieved from the Scopus database, covering publications related to the acceptance and adoption of technology in government from 2020 to 2025. The network visualization results indicate that artificial intelligence (AI), digital governance, public transport, e-health, and COVID-19 are among the dominant research themes, reflecting the rapid adoption of technology in transforming public services. The cooccurrence analysis reveals strong linkages among topics such as public health, AI, blockchain, and public trust, underscoring the increasing integration of digital technologies within governance systems. Furthermore, the overlay visualization demonstrates a thematic shift from fundamental studies on acceptance factors—such as trust, security, and digital literacy— toward implementation-oriented strategies, including digital transformation, smart governance, and public service efficiency. The findings suggest that technology adoption in public service continues to expand and diversify; however, significant challenges remain, particularly concerning data security, transparency, and citizen trust. Future research should focus on exploring the application of AI, the use of blockchain for governance, and the integration of internet of things (IoT) in smart city development to support a sustainable, efficient, and citizen-centric digital transformation in the public sector.